2006
DOI: 10.1128/jcm.44.1.260-265.2006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Locus Variable-Number Tandem Repeat Analysis for Typing of Staphylococcus epidermidis

Abstract: We applied a high-resolution PCR-based typing method, multiple-locus variable-number tandem repeat analysis (MLVA), for discrimination of 30 multidrug-resistant clinical isolates of Staphylococcus epidermidis. The results of MLVA were congruent with results obtained by pulsed-field gel electrophoresis (PFGE). MLVA generated discrete character data, and its discriminatory capacity was comparable to that of PFGE.The clinical significance of Staphylococcus epidermidis is increasingly recognized. The bacterium is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
(15 reference statements)
1
27
0
Order By: Relevance
“…However, previously published schemes using five tandem repeat loci in Chlamydia abortus (Laroucau et al, 2009), S. epidermidis (Johansson et al, 2006), and Salmonella enterica (Lindstedt et al, 2004) have shown satisfactory discrimination. Other studies comparing MLVF to MLST have also shown a good concordance between type assignment made by the two methods (Malachowa et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…However, previously published schemes using five tandem repeat loci in Chlamydia abortus (Laroucau et al, 2009), S. epidermidis (Johansson et al, 2006), and Salmonella enterica (Lindstedt et al, 2004) have shown satisfactory discrimination. Other studies comparing MLVF to MLST have also shown a good concordance between type assignment made by the two methods (Malachowa et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…The high frequency of this transposon in this study might be due to the origin of the isolates, as we did not focus on hospital strains and some of the strains were isolated from outpatients. On the other hand, the presence of IS256 among most of the biofilm-producing strains, which were positive for icaA, icaD and atlE genes, showed the correlation between these factors and clinically relevant strains (10,25,42).…”
Section: Discussionmentioning
confidence: 99%
“…The MLVA was performed for S. epidermidis isolates, using seven VNTR loci, including SE2395, SE0331, SE 828, SE1632, SE0175, Se2, and Se4, as previously described (16,17). Polymerase chain reaction was performed for each locus in a 25-µL volume PCR reaction containing specific primers (Pishgam biotech, Iran).…”
Section: Multi Locus Vntr Analysis (Mlva) and Agr Typingmentioning
confidence: 99%
“…Genotypic and phenotypic diversity have been created due to point mutation, recombination or other addition methods as well as deletion of mobile genetic elements (14). Different methods of typing and criteria are used to determine the closeness of strains, although time and place should also be considered (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%